Clustering or competition? The foreign investment behaviour of German banks - Alexander Lipponer; Claudia M. Buch (Deutsche Bundesbank, 2004)
The presence of other firms in a foreign market can have a double-edged effect on the profitability of new entrants. Firstly, a larger presence of other firms implies more competition and thus lowers the earnings prospects of new entrants. Secondly, there might be positive spill-over effects between the activities of new and old entrants, which can lead to clustering effects. Such clustering of firms in foreign markets has been documented in the empirical literature on foreign direct investment (FDI) of nonfinancial firms, but little evidence is available for banks. This paper analyses whether banks have a tendency to cluster abroad and whether smaller banks in particular invest in markets where other banks are already present. We use firm-level evidence on the foreign direct investments of German banks for the period 1997-2000 to test this hypothesis. Our results suggest that German banks are indeed more active in markets in which other German banks are already present. However, once we control for countryfixed effects, the negative competition effect dominates.
Keywords: F21; F0; 330; international banking; clustering; foreign direct investment; Bank; Direktinvestition; Deutsch; Regionale Konzentration; Schätzung; Deutschland